The pharmacology of tacrine at N-methyl-d-aspartate receptors - Horak, Martin; Holubova, Kristina; Nepovimova, Eugenie; Krusek, Jan; Kaniakova, Martina; Korabecny, Jan; Vyklicky, Ladislav; Kuca, Kamil; Stuchlik, Ales; Ricny, Jan; Vales, Karel; Soukup, Ondrej (Progress in neuro-psychopharmacology & biological psychiatry, 2017)
The mechanism of tacrine as a precognitive drug has been considered to be complex and not fully understood. It has been reported to involve a wide spectrum of targets involving cholinergic, gabaergic, nitrinergic and glutamatergic pathways. Here, we review the effect of tacrine and its derivatives on the NMDA receptors (NMDAR) with a focus on the mechanism of action and biological consequences related to the Alzheimer's disease treatment. Our findings indicate that effect of tacrine on glutamatergic neurons is both direct and indirect. Direct NMDAR antagonistic effect is often reported by in vitro studies; however, it is achieved by high tacrine concentrations which are not likely to occur under clinical conditions. The impact on memory and behavioral testing can be ascribed to indirect effects of tacrine caused by influencing the NMDAR-mediated currents via M1 receptor activation, which leads to inhibition of Ca2+-activated potassium channels. Such inhibition prevents membrane repolarization leading to prolonged NMDAR activation and subsequently to long term potentiation. Considering these findings, we can conclude that tacrine-derivatives with dual cholinesterase and NMDARs modulating activity may represent a promising approach in the drug development for diseases associated with cognitive dysfunction, such as the Alzheimer disease.
Keywords: Neurons; receptory N-methyl-D-aspartátu; membránové potenciály; Models, Molecular; Cognition; cholinesterasové inhibitory; takrin; Tacrine; Cholinesterase Inhibitors; M1 activation; Receptors, N-Methyl-D-Aspartate; Long term potentiation; Membrane Potentials; molekulární modely; zvířata; Humans; neurony; NMDA receptors; Multi-target directed ligands; lidé; Animals